The caridean shrimps(Crustacea Decapoda) of the Albatross Philippine expedition, 1907-1910 part 4 families Oplophoridae and Nematocarcinidae - Chace, Fenner A., Jr (Smithsonian Institution Press, 1986)
Smithsonian contributions to zoology; no.381